Customer Dissatisfaction Index and its Improvement Costs - Lvovs, Aleksandrs; Mutule, Anna (Electrical, Control and Communication Engineering, 2010)
The paper gives description of customer dissatisfaction index (CDI) that can be used as reliability level characterizing factor. The factor is directly joined with customer satisfaction of power supply and can be used for control of reliability level of power supply for residential customers. CDI relations with other reliability indices are shown. Paper also gives a brief overview of legislation of Latvia in power industry that is the base for CDI introduction. Calculations of CDI improvement costs are performed in the paper too.